PREPARATION OF FOUR NEW ANTIBIOTICS FROM A MUTANT OF Streptomyces fradiae - Shier, W. Thomas (1969)
A mutant of Streptomyces fradiae 3535 incapable of synthesizing the antibiotic neomycin in the absence of added deoxystreptamine, the aminocyclitol subunit of the antibiotic, has been isolated from a culture treated with N-methyl-N′-nitro-N-nitrosoguanidine. The related aminocyclitols streptamine and 2-epistreptamine, both available by chemical synthesis, were incorporated by the mutant strain into four new antibiotics, for which we suggest the names hybrimycins A (isomers 1 and 2, from streptamine) and hybrimycins B (isomers 1 and 2, from 2-epistreptamine). Structures of the new antibiotics were established from the mass spectral, nuclear magnetic resonance, and optical rotatory properties of appropriate derivatives. This method offers a promising approach to the synthesis of other antibiotics.